Understanding the possibility of material release from end-of-life solar modules: A study based on literature review and survey analysis. (November 2020) - Nain, Preeti; Kumar, Arun
Abstract: The present study addresses the aspect of upcoming stream of photovoltaic waste by investigating the possibility of material release from end-of-life solar modules using an integrated approach of literature review and stakeholders survey. It involved (i) identification of failure events responsible for degradation of photovoltaic modules as per literature review, (ii) evaluation of identified events by a survey of stakeholders of photovoltaic industry and (iii) investigation of solar industry's stakeholders' perceptions on events responsible for generation of end-of-life modules, and present management and recycling practices, (iv) fault tree analysis for estimating probability of material release, and (v) calculation of risk priority number for finding severity of failure events responsible for dumping and material leaching from solar modules. An assessment of previous studies on degradation of solar modules indicates that environmental factors, like high UV irradiation, humidity, temperature play significant roles in module degradation. As per survey, more than 90% of manufacturers were involved in crystalline-silicon photovoltaic business. Only 20% manufacturers replied when asked on the aspect of end-of-life modules, showing that the photovoltaic waste is comparatively a new subject and not enough discussion have been devoted to it. Lack of recycling infrastructure, incentives, and environmental awareness significantly influence recycling and recuse practices. On the basis of worst-case scenario, the maximum probability of the material release from dumped solar panels was estimated to be 0.053. As per manufacturer's opinion, the most critical factors resulting in modules failure are glass breakage and encapsulant degradation. Among various events from manufacturing to end-of-life stage, the module breakage during operation event have highest probability value (i.e., 0.313). Risk priority number analysis suggests that generation of end-of-life photovoltaic and environmental damage resulting to metal leaching as the most significant events. Damage during manufacturing and installation were identified to be the least significant events resulting in degradation. At present, 76% producers do not recycle or reuse photovoltaic waste material, preferably sell them to informal waste recyclers or rag pickers. Findings from the present study highlight the urgency to develop a suitable system for collection and management of end-of-life modules. Highlights: Identification of failure events responsible for generating end-of-life photovoltaic waste. Risk priority number analysis suggests that environmental damage is most significant event. As per fault tree analysis, there is a 5.3% chance of material release from dumped modules. 76% producers do not recycle photovoltaic waste, prefer to sell them to informal recyclers. Lack of recycling incentives is the significant barrier in end-of-life solar waste management.